Measurement of entrance surface air kerma by using direct method: a comparison study - Roslan, Nur Amanina Izzati Mohd (Universiti Sains Malaysia, 2016)
Dosimetry has increasing its importance in the radiation safety culture and protection purpose. Assessment of entrance skin doses in conventional diagnostic radiology should be evaluated in order minimizing hazard in delivering optimum radiation dose amount. The entrance surface air kerma was determined by directly measured using TLDs in two common radiography examination PA chest and abdomen. Results were analyzed in variable objectives according to this study. Measurement using direct method done with selected parameter from the previous study by Taha et al., 2014. For parameter 81 kVp with 12.5mAs for anterioposterior (AP) projection of the abdomen, mean dose obtained was 1.96 mGy compared to previous study which value 2.50 mGy. were For chest radiograph procedure, parameter of were 125 kVp, 1.6 mAs, for posterioanterior (PA) projection give the mean dose of 0.21 mGy than the previous study at 0.14mGy. Eventhough the values does not achieved in similar, ESAK was still below the reference level suggested by IAEA (2004), 0.3 mGy for chest PA, and 10 mGy for abdomen AP. The result of this study showed that the ESAK values were still in acceptable range doses from common radiological examinations. Method of calculation can be used if the TED was available for ESAK measurement if its deviation quite small.